A new labour law for platform workers and umbrella companies. (1st December 2018) - Pietro Ichino
Abstract : This article highlights one aspect of technological evolution which impacts the labour market and, consequently, our labour law systems: the advent of so-called labour platforms, entailing disintermediation in the matching of supply and demand for labour. It examines the prospects for the future development of instruments aimed at ensuring that platform workers obtain a minimum level of adequate occupational, financial and welfare security.